INTEGRASI ILMU PENGETAHUAN DALAM PENDIDIKAN ISLAM: (Analisis Pemikiran KH. Ahmad Sanusi dalam Tafsir Tamsiyat Al-Muslimin dan Malja' Al-Thalibin) - Ahmad Riva Al Faruqi; Anna Ropitasari; Lutfi (LPPM Institut Nida El-Adabi, 2024)
The integration between science and religion, especially Islam, is becoming increasingly relevant in the era of globalization. This research aims to examine Sanusi's thinking about the integration of science and the obligations of Muslims in mastering the knowledge of the world and the hereafter. Through a critical analysis of Sanusi's interpretation of the verses of the Qur'an, this study seeks to uncover how Sanusi articulates the importance of science in the religious context and daily life of Muslims. The research method used is a qualitative method with a descriptive-analytical approach. The data was collected through a literature study involving Sanusi's works, including Qur'anic commentaries, books, and other relevant writings. In addition, textual analysis was carried out on the verses of the Qur'an that became the basis of Sanusi's thinking about science. The results of the study show that Sanusi firmly rejects the dichotomy between religious science and world science. He emphasized that the two types of knowledge must be integrated to achieve the perfect balance of life for Muslims. Sanusi also harshly criticized Muslims who ignore the world's science, considering them no different from animals that do not take advantage of the reason and knowledge given by Allah. His thoughts highlight the importance of natural science as a means to know God's greatness and increase faith. In addition, Sanusi emphasized that mastery of science is the key to achieving progress and overcoming colonialism. Thus, this study confirms that the integration of natural sciences and religion, as proposed by Sanusi, is an important foundation for the development of education and the advancement of Muslims in the modern era.